Dielectric Pyrochlores in Bismuth Magnesium Tantalate Ternary System / Tan Kar Ban … [et al.] - Kar Ban, Tan; Zainal, Zulkarnain; Chwin Chieh, Khaw; Phei Yi, Tan; Soo Kien, Chen (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The present invention relates to the synthesis and characterization of bismuth magnesium tantalate dielectrics (BMT pyrochlores), and to their structural and electrical properties. Ceramic compositions produced in this invention include Bi3^Mg2Ta3O14, Bi2Mg2/3Ta4/3O7 and Bi3+(5/2)xMg2-xTa3-(3/2)xO14-x; phase pure sub solidus solution as represented by Bi3+(5/2)xMg2-xTa3-(3/2)xO14-x, wherein 0.12 < x < 0.22 able to be produced. This invention also discloses a method of preparation of the BMT pyrochlore, in which Bi2O3, MgO and Ta2O5 in stoichiometric amounts are mixed homogeneously with acetone, pre-treated at 300 °C to 600 °C for at least one hour to ensure that the Bi2O3 reacts to form less-volatile compounds, the pre-treated powders are subsequently heated at 800 °C overnight, and further synthesized at 1025 °C for 48 hours, preferably with intermediate regrinding. The compositions of invention have outstanding bulk dielectric properties, e.g. e' values of between 74 - 85 at frequency 1 MHz at ~25oC, TCe' of -158 to -328 ppm/°C at 1 MHz in the range of ~25°C - 300°C and tan 6 in the order of 10-3 at 1 MHz, ~25oC. The bismuth magnesium tantalate dielectrics are suitable particularly for ceramic based capacitor application.